Cardiac Resynchronisation Therapy in Patients with Moderate to Severe Heart Failure in Germany: A Cost-Utility Analysis of the Additional Defibrillator - Moritz Hadwiger; Fabian-Simon Frielitz; Nora Eisemann; Christian Elsner; Nikolaos Dagres; Gerhard Hindricks; Alexander Katalinic (Applied Health Economics and Health Policy, 2020)
Background: Cardiac resynchronisation therapy (CRT) is a well-established form of treatment for patients with heart failure and cardiac dyssynchrony. There are two different types of CRT devices: the biventricular pacemaker (CRT-P) and the biventricular defibrillator (CRT-D). The latter is more complex but also more expensive. For the majority of patients who are eligible for CRT, both devices are appropriate according to current guidelines. The purpose of this study was to conduct a cost-utility analysis for CRT-D compared to CRT-P from a German payer's perspective. Methods A cohort Markov-model was developed to assess average costs and quality-adjusted life-years (QALY) for CRT-D and CRT-P. The model consisted of six stages: one for the device implementation, one for the absorbing state death, and two stages (“Stable” and “Hospital”) for either a CRT device or medical therapy. The time horizon was 20~years. Deterministic and probabilistic sensitivity analyses and scenario analyses were conducted. Results The incremental cost-effectiveness ratio (ICER) of CRT-D compared with CRT-P was exteuro24,659 per additional QALY gained. In deterministic sensitivity analysis, the survival advantage of CRT-D to CRT-P was the most influential input parameter. In the probabilistic sensitivity analysis 96% of the simulated cases were more effective but also more costly. Conclusions Therapy with CRT-D compared to CRT-P resulted in an additional gain of QALYs, but was more expensive. In addition, the ICER was subject to uncertainty, especially due to the uncertainty in the survival benefit. A randomised controlled trial and subgroup analyses would be desirable to further inform decision making.
Keywords: 610; Pharmacoeconomics and Health Outcomes; Quality of Life Research; Health Economics; Health Administration; Public Health